2019
DOI: 10.1080/15384101.2019.1656476
|View full text |Cite
|
Sign up to set email alerts
|

α-Fodrin is required for the organization of functional microtubules during mitosis

Abstract: The cytoskeleton protein α-fodrin plays a major role in maintaining structural stability of membranes. It was also identified as part of the brain γ-tubulin ring complex, the major microtubule nucleator. Here, we investigated the requirement of α-fodrin for microtubule spindle assembly during mitotic progression. We found that α-fodrin depletion results in abnormal mitosis with uncongressed chromosomes, leading to prolonged activation of the spindle assembly checkpoint and a severe mitotic delay. Further, α-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 50 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…CENP-E, a mitotic motor, carries chromosomes through the spindle with help from detyrosinated tubulin. We reported that ␣-fodrin-deficient cells displayed reduced detyrosinated tubulin (58). This could have important implications for the involvement of ␣-fodrin in the progression of cancer.…”
Section: Functions Exclusive To Fodrinmentioning
confidence: 75%
“…CENP-E, a mitotic motor, carries chromosomes through the spindle with help from detyrosinated tubulin. We reported that ␣-fodrin-deficient cells displayed reduced detyrosinated tubulin (58). This could have important implications for the involvement of ␣-fodrin in the progression of cancer.…”
Section: Functions Exclusive To Fodrinmentioning
confidence: 75%
“…U-251 MG cells were treated with control shRNA/α-fodrin shRNA for 96 h to achieve appreciable downregulation of α-fodrin expression. The shRNA used for these experiments has beendetailed in our previous publication [ 5 ]. The cells were then harvested and total protein was extracted using RapiGest TM SF (Waters Corporation, Milford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The literature survey also revealed diverse functions of this protein. Further, we have been able to show that α-fodrin is important in chromosome congression and mitotic progression in cells [ 5 ]. It is also important in calcium-based signaling, especially in neuronal cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To replace the dicey SMG-based therapy, there are numerous works citing or implicating cytoskeleton perpendicular move relative to the cell polarity axial orientation [49] [50] [51]. These works showed that the resultant cells in such orientations relative to surrounding cells had attained movability which has had special attention in metastasis [6] [7] [52] [53].…”
Section: The Likelihood That Genes Determining the 90˚ Cytoskeleton Turn Can Be Therapy Targetedmentioning
confidence: 99%